Characterization of hyperalkaline fluids produced by low‐temperature serpentinization of mantle peridotites in the Oman and Ligurian ophiolites. (31st July 2013) - Chavagnac, Valérie; Monnin, Christophe; Ceuleneer, Georges; Boulart, Cédric; Hoareau, Guilhem
Abstract : [1] A regional survey of alkaline springs in Oman and Ligurian ophiolites shows that the alkaline water compositions significantly vary from one ophiolite to the other and within the same ophiolite. The first‐order correlation between the Na (and K) and Cl concentrations points to fluid compositions only partly due to evaporation. The scatter around the evaporation line implies that Na and Cl may not be conservative during the alteration of the ultramafic rocks. Mg is almost entirely depleted at pH > 10.5 as a result of serpentine formation within the ultramafic body and of brucite (and minor hydrotalcite) precipitation at the springs. Ca accumulates in the high‐pH fluids and is consumed by Ca‐carbonate formation at the springs, by mixing with river waters or by the CO2 supply from the atmosphere. Thermodynamic calculations show that brucite saturation is reached at pH values around 10.5 which triggers major changes in the water composition. The waters evolve from a quartz‐saturated low‐pH continental environment to a brucite‐dominated high‐pH serpentinizing system at low temperature. The highest water salinities are found in springs located along the basal thrust plane of the ophiolite. The highest Al concentrations are found in some springs located on the crustal side of the mantle/crust boundary. This poses the question of the hydrologic pathways and of the role of the mineralogical composition of the altered formations. Key Points: New temperature and composition of the alkaline waters Brucite formation at pH 10.5 triggers major chemical and mineralogical changes Relationship between the water compositions and the hydrologic pathways